Reactions of [FeFe]-hydrogenase with carbon monoxide and formaldehyde - Foster, C; Carina Foster (2012)
The use of H2 as an energy carrier has in recent years been identified as a promising future solution to the current energy crisis. Hydrogenases are metalloenzymes found in many microorganisms and are used to catalyse the reversible inter-conversion of protons and H2. These enzymes and their synthetic analogues have been recognised as a way to facilitate the use of H2 as a fuel. A major challenge to the future use of these catalysts is their reactions with small molecule inhibitors, such as oxygen and carbon monoxide. Detailed understanding of the structure and catalytic mechanism of these highly efficient catalysts is vital for the design of bio-inspired functional analogues for use in technological applications. In this thesis electrochemical studies of three [FeFe]-hydrogenases are presented, performed using the technique of protein film electrochemistry. The strong potential dependence of the reaction of these hydrogenases with carbon monoxide and formaldehyde is characterised and rationalised. These studies provide compelling evidence for the formation of a previously ambiguous super-reduced state of [FeFe]-hydrogenase at low potential. This state is shown to be active and stable, and it is proposed that this state is involved in catalytic H2 production. This super-reduced state is shown to have a high affinity for the reversible binding of formaldehyde, but a very low affinity for both carbon monoxide and oxygen. Activation of carbon monoxide inhibited [FeFe]-hydrogenase can be very rapidly induced by the application of a sufficiently reducing potential. These enzymes, considered to be oxygen sensitive, are shown to be extremely tolerant to irreversible oxygen damage at very reducing potentials where the super-reduced state is formed.